A MEMS Micro Force Sensor Based on A Laterally Movable Gate Field-Effect Transistor (LMGFET) with A Novel Decoupling Sandwich Structure. (February 2023) - Gao, Wendi; Qiao, Zhixia; Han, Xiangguang; Wang, Xiaozhang; Shakoor, Adnan; Liu, Cunlang; Lu, Dejiang; Yang, Ping; Zhao, Libo; Wang, Yonglu; Wang, Jiuhong; Jiang, Zhuangde; et al.
Abstract: This paper presents the development of a novel micro force sensor based on a laterally movable gate field-effect transistor (LMGFET). A precise electrical model is proposed for the performance evaluation of small-scale LMGFET devices and exhibits improved accuracy in comparison with previous models. A novel sandwich structure consisting of a gold cross-axis decoupling gate array layer and two soft photoresistive SU-8 layers is utilized. With the proposed dual-differential sensing configuration, the output current of the LMGFET lateral operation under vertical interference is largely eliminated, and the relative output error of the proposed sensor decreases from 4.53% (traditional differential configuration) to 0.01%. A practicable fabrication process is also developed and simulated for the proposed sensor. The proposed LMGFET-based force sensor exhibits a sensitivity of 4.65 µA·nN −1, which is comparable with vertically movable gate field-effect transistor (VMGFET) devices, but has an improved nonlinearity of 0.78% and a larger measurement range of ±5.10 µN. These analyses provide a comprehensive design optimization of the electrical and structural parameters of LMGFET devices and demonstrate the proposed sensor's excellent force-sensing potential for biomedical micromanipulation applications.